The Role of Financial Literacy, Financial Attitudes, and Family Financial Education on Personal Financial Management and Locus of Control of University Students - Haudi, Haudi (IJOSMAS, 2023)
The purpose of this study was to analyze the direct and indirect effects of financial literacy, financial attitudes, and family financial education on personal financial management with locus of control as an intervening variable. This study uses an explanatory research approach, which aims to explain the causal relationship between the research variables and hypothesis testing. This type of research is a type of associative and quantitative research. To examine how a variable relates or relates to other variables, or whether a variable is influenced by other variables. This type of research is a type of associative and quantitative research. Respondents in this study were university students in Banten as many as 321 students. Research data was obtained by distributing online questionnaires designed with a Likert scale of 1 to 7 via social media. The sampling method in this study used a non-probability sampling method which was determined by the simple random sampling method. Data collection techniques used online questionnaires, while data analysis techniques in this study used Structural Equation Modeling (SEM) analysis. The results of this study are financial literacy has a positive and significant effect on personal financial management, financial attitudes have a positive and significant effect on personal financial management, family financial education has a positive and significant effect on personal financial management, financial literacy has a positive and significant effect on locus Of Control, Financial Attitude has a positive and significant effect on Locus Of Control, Family Financial Education has a positive and significant effect on Locus Of Control, Locus Of Control has a positive and significant effect on Locus Of Control.